Detection of culturable and viable but non‐culturable cells of beer spoilage lactic acid bacteria by combined use of propidium monoazide and horA‐specific polymerase chain reaction. Issue 1 (4th January 2016) - Deng, Yang; Zhao, Junfeng; Li, Huiping; Xu, Zhenbo; Liu, Junyan; Tu, Jingxia; Xiong, Tao
Abstract : Current methods of detecting beer spoilage lactic acid bacteria (LAB) are time‐consuming and do not differentiate between viable and non‐viable bacteria. In this study, a combination of the conventional polymerase chain reaction (PCR) and propidium monoazide (PMA) pretreatment has been described to circumvent the disadvantages. The horA ‐specific PMA‐PCR described here identifies beer spoilage LAB based not on their identity, but on the presence of a gene that is shown to be highly correlated with the ability of LAB to grow in beer. The results suggest that the use of 20 µg/mL or less of PMA did not inhibit the PCR amplification of DNA derived from viable, but putatively non‐culturable (VPNC) Lactobacillus acetotolerans . The minimum amount of PMA to completely inhibit the PCR amplification of DNA derived from dead L . acetotolerans cells was 1.5 µg/mL. The detection limit of established PMA‐PCR assays was found to be 100 VPNC cells/reaction for the horA gene. Furthermore, the horA ‐specific PMA‐PCR assays were subjected to 18 reference strains, representing 100% specificity with no false positive amplification observed. In conclusion, the use of horA ‐specific PMA‐PCR allows for a substantial reduction in the time required for the detection of potential beer spoilage LAB and efficiently discriminates between live and dead cells. Copyright © 2016 The Institute of Brewing & Distilling